Sociodemographic characteristics and bone health in Argentine adults with a plant-based diet: Características sociodemográficas y salud ósea en adultos argentinos con alimentación basada en plantas - Taboada, Paula (2024)
Objective: To analyze the sociodemographic characteristics and bone health among adult consumers of plant-based diets (PBD). Methods: Individuals aged 18 to 75 were invited to complete a self-administered survey via a digital platform. Results: A total of 1151 participants completed the survey; the majority were women [n=958 (83.2%)], young [age (years): 18-25: 35.8%; 26-35: 39.8%, and 36-45: 17.4%] and single (67.1%). The pattern of PBD consumption was mainly represented by veganism (54.0%), followed by lacto-ovo-vegetarianism (27.7%). The primary reason for their dietary choice was animal welfare (83.5%). Adherence to PBD, based on duration (years), was <1: 12.3%; 1-5: 67.4%; 10-15: 14.8%, and >15: 5.5%. 16% of vegans reported having experienced fractures, and 5.1% reported undergoing bone densitometry. Of these, 88.1% reported normal results, and 11.8% presented osteopenia. No cases of osteoporosis were recorded in the survey. Vitamin B12 was the predominant supplement among PBD consumers (61.4%). Conclusions: PBD consumers constitute a significant minority in our country, predominantly composed of women under 35 years old, with a projected increase in the coming years.